H-infinity based modified droop control method for voltage and frequency regulation of an islanded microgrid supplying non-linear and unbalanced loads - Sharma, Pramod; Adhikari, Ananta; Khanal, Sujan (Himalayan Journal of Applied Science and Engineering, 2025)
This paper presents an advanced control method for islanded microgrid (MG) based on the H-infinity (H∞) controller. The proposed method is designed to regulate system voltage and frequency within acceptable ranges under disturbances caused by load variations. The method is also used to ensure equal power sharing by each voltage source inverters (VSIs). To evaluate its effectiveness, the proposed controller is compared with conventional droop controller. In this approach, the droop control loop, along with the current and voltage control loops, is optimized effectively to manage variations in the system load. The method incorporates repetitive control principles with internal model concept to achieve precise tracking of voltage and current errors. The proposed system model consists of three voltage source inverters (VSIs), linear, nonlinear and unbalanced loads. The performance and feasibility of the proposed method is evaluated through MATLAB/Simulink simulations, including FFT analysis for harmonic assessment. The Comparative analysis with the traditional droop control method demonstrates the superior performance of the proposed method in managing microgrid operation in islanded mode.